Developing strategies to reduce the risk of hazardous materials transportation in Iran using the method of fuzzy swot analysis - Kheirkhah, Amir S.; Esmailzadeh, Ali; Ghazinoory, Sepehr (Transport, 2009)
An increase in hazardous materials transportation in Iran along with the industrial development and increase of resulted deadly accidents necessitate the development and implementation of some strategies to reduce these incidents. SWOT analysis is an efficient method for developing strategies, however, its structural problems, including a lack of prioritizing internal and external factors and inability to consider two sided factors reducing its performance in the situations where the number of internal and external factors affecting the risk of hazardous materials is relatively high and some factors are two sided in nature are presented in the article. Fuzzy SWOT analysis is a method the use of which helps with solving these problems and is the issue of employing an effective methodology. Also, the article compares the resulted strategies of the fuzzy method with the strategies developed following SWOT in order to show the relative supremacy of the new method. First published online: 27 Oct 2010